PENDEKATAN SAINTIFIK DAN MEDIA MODIFIKASI UNTUK MENINGKATKAN HASIL BELAJAR TOLAK PELURU GAYA ORTODOK PELAJAR SEKOLAH MENENGAH ATAS KELAS XII - Robi Hidayat Tumanggor; Sabaruddin Yunis Bangun (JURNAL HANDAYANI PGSD FIP UNIMED, 2023)
The goal of this study was to ascertain how class XII junior high school students learned after receiving conventional style input using a scientific method and changed media. Students in class XII at a high school are the research subjects for this classroom action research study. SMA Negeri 3 Negeri Medan has 40 pupils, including 18 males and 22 girls. The Toss Ball Process Assessment Form was the tool employed in this study. The raw data used in the research was collected from SMA Negeri 3 Medan students in class XII. Eight (20%) of the 40 students—who had an average mark of 61.04—reached the master's level, whereas 32 (80%) did not.The results of the first cycle: S1 failed 22 students (55%) and S2 achieved 18 of 40 students (45%), the average value of students 69.4. In fall II, 6 students (15%) failed the exam, and 34 students (85%) out of 40 students achieved an average maturity level of 82.7. This means that classical learning ability (≥85%) has been achieved. The conclusion of this study is that a scientific approach and modified media can be used to improve the academic achievement of class XII students using orthodox media.Keyword: Enhancement, Scientific Approach, Modification of Learning, Learning Outcomes, Shot Put Abstrak: Tujuan penelitian ini adalah untuk mengetahui hasil belajar input gaya ortodoks dengan pendekatan saintifik dan media modifikasi pada peserta didik SMP kelas XII di SMA Negeri 3 Negeri Medan. Subjek penelitian ini adalah 40 siswa dari kelas XII, terdiri dari 18 laki-laki dan 22 perempuan. Metode penelitian ini adalah penelitian tindakan kelas. Data penelitian ini didasarkan pada data mentah dari siswa kelas XII SMA Negeri 3 Medan. Penelitian ini menggunakan formulir Penilaian Proses Toss Ball. Dari 40 siswa, 32 tidak lulus (80%) dan 8 (20% dari total) mencapai magister dengan nilai rata-rata 61,04. Siklus I hasil:  S1 gagal 22 peserta didik (55%)  dan S2 tercapai 18  dari 40 peserta didik (45%), nilai rata-rata  peserta didik 69,4. Pada musim gugur II, 6 peserta didik (15%) gagal dalam ujian, dan 34 peserta didik (85%) dari 40 peserta didik mencapai tingkat kematangan rata-rata 82,7. Artinya kemampuan belajar klasikal (≥85%) telah tercapai. Kesimpulan dari penelitian ini adalah pendekatan saintifik dan media modifikasi dapat digunakan untuk meningkatkan prestasi akademik peserta didik kelas XII dengan menggunakan media  ortodoks.Kata Kunci: Peningkatan, Pendekatan Saintifik, Modifikasi Pembelajaran, Hasil Belajar, Tolak Peluru